Inverse Relationship of the CMKLR1 Relative Expression and Chemerin Serum Levels in Obesity with Dysmetabolic Phenotype and Insulin Resistance - Fernanda-Isadora; Rosa-Elena N; Sandra-Lu; Perla-Monserrat Ma; Jorge Castro-Albarrán; Efraín Chavarría-Ávila; Milton-Omar; Eduardo Gómez-Bañuelos; Marcelo-Herón Petri; Joel-Isidro R; María-Elena A; Clara Ríos-Ibarra; et al. (Hindawi Limited, 2016)
Background. In obesity there is a subclinical chronic low-grade inflammatory response where insulin resistance (IR) may develop. Chemerin is secreted in white adipose tissue and promotes low-grade inflammatory process, where it expressed CMKLR1 receptor. The role of chemerin and CMKLR1 in inflammatory process secondary to obesity is not defined yet. Methods. Cross-sectional study with 134 individuals classified as with and without obesity by body mass index (BMI) and IR. Body fat storage measurements and metabolic and inflammatory markers were measured by routine methods. Soluble chemerin and basal levels of insulin by ELISA and relative expression of CMKLR1 were evaluated with qPCR and 2-ΔΔCT method. Results. Differences (P<0.05) were observed between obesity and lean individuals in body fat storage measurements and metabolic-inflammatory markers. Both CMKLR1 expression and chemerin levels were increased in obesity without IR. Soluble chemerin levels correlate with adiposity and metabolic markers (r=8.8% to 38.5%), P<0.05. Conclusion. The increment of CMKLR1 expression was associated with insulin production. Increased serum levels of chemerin in obesity were observed, favoring a dysmetabolic response. The results observed in this study suggest that both chemerin and CMKLR1 have opposite expression in the context of low-grade inflammatory response manifested in the development of IR.